Characteristics of defecation sites in the Geoffroy’s cat Leopardus geoffroyi - Soler, Lucia (2009)
Little is known about the use of feces in scent marking by small wildcats. We analyzed the characteristics of 357 Geoffroy’s cat, Leopardus geoffroyi, defecation sites in five protected areas of Argentina. Defecation sites were mainly found in trees (47.6%) or on the ground (38.1%), and the frequency of occurrence of the types of sites differed between areas. Almost half (47.3%) of defecation sites were latrines, with 6.1 ± 3.6 (mean ± SD) feces each. Geoffroy’s cats were flexible in the choice of defecation sites, but mainly deposited feces in latrines located in conspicuous sites. These results suggest that Geoffroy’s cats use feces in olfactory/visual communication.